Kunst im Hotel The Ritz-Carlton Wolfsburg. - Schneider, Maria; Schulze, Horst (Wolfsburg : Autostadt, 2000)
Blossfeldt, Karl ; Förg, Gunther ; Heidersberger, Heinrich ; Kawamata, Nangaku ; Kenna, Michael ; Kinold, Klaus ; Kumrow, Klaus ; Mapplethorpe, Robert ; Newman, Arnold ; van Ofen, Michael ; Pare, Richard ; Roberts, Perry ; Struth, Thomas ; Tremlett, David ; Wick, Cecile
keerdruk
Duits & Engels
boek